2020
DOI: 10.1039/d0sc02976a
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and vibrational surface-enhanced Raman scattering: from atomically defined Au(111) and (100) to roughened Au

Abstract: In surface-enhanced Raman spectra, vibrational peaks are superimposed on a background continuum, which is known as one major experimental anomaly. This is problematic in assessing vibrational information especially in the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 74 publications
(125 reference statements)
3
51
0
Order By: Relevance
“… 35 A shortcoming of commonly used SERS substrates such as roughened metal surfaces or colloidal aggregates is that they give rise to spectra of limited reproducibility regarding intensity and appearance. 36 These limitations originate from the heterogeneity of the plasmonic resonances present on the substrate as well as the stochastic placement of individual sample molecules with respect to local electromagnetic hotspots. On the other hand, TERS probes like the one used in this study can be fabricated with a high degree of reproducibility and a precisely tuned plasmonic resonance behavior (see Methods ).…”
Section: Results and Discussionmentioning
confidence: 99%
“… 35 A shortcoming of commonly used SERS substrates such as roughened metal surfaces or colloidal aggregates is that they give rise to spectra of limited reproducibility regarding intensity and appearance. 36 These limitations originate from the heterogeneity of the plasmonic resonances present on the substrate as well as the stochastic placement of individual sample molecules with respect to local electromagnetic hotspots. On the other hand, TERS probes like the one used in this study can be fabricated with a high degree of reproducibility and a precisely tuned plasmonic resonance behavior (see Methods ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…For comparison of scattering responses in the anti‐Stokes and Stokes branches, ultranarrow band notch filters (reflecting volume Bragg grating, OptiGrate Corp) was used to remove the Rayleigh scattering under excitation of 1.96 eV (NEO‐30MS1, NEOARK). [ 8,17 ]…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several studies showed that the origin of the SERS background on Au surface can be well explained by ERS rather than PL. [ 6–8 ] For other metals, however, the origin of the background generation is still under discussion. Such controversy about the mechanism is partly due to a lack of information about ERS in metals; the cross section of ERS in noble metals is generally very small.…”
Section: Introductionmentioning
confidence: 99%
“…Next, determination of the in situ SERS Stokes ( I s ) and anti-Stokes ( I as ) intensities was further carried out to quantify the laser-induced temperature rise at the junction of the metal particles ( i.e., hot spots) 14 on self-assembled GNP arrays of 100.9 nm (GNP1) and 42.7 nm (GNP2), respectively. On each array, the laser with 10, 25, 50, and 100% of full power generated four spectral lines, respectively (Fig.…”
mentioning
confidence: 99%